2013
DOI: 10.3724/sp.j.1141.2012.01001
|View full text |Cite
|
Sign up to set email alerts
|

Two bacterial infection models in tree shrew for evaluating the efficacy of antimicrobial agents

Abstract: Animal models are essential for the development of new anti-infectious drugs. Although some bacterial infection models have been established in rodents, small primate models are rare. Here, we report on two bacterial infection models established in tree shrew (Tupaia belangeri chinensis). A burnt skin infection model was induced by dropping 5×106 CFU of Staphylococcus aureus on the surface of a wound after a third degree burn. This dose of S. aureus caused persistent infection for 7 days and obvious inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Li et al (2012) found that tree shrews are susceptible to Staphylococcus aureus and Pseudomonas aeruginosa . Zhan et al (2014) infected Chinese tree shrews with Mycobacterium tuberculosis and found that infected animals developed serious symptoms similar to the clinical signs of active tuberculosis observed in humans.…”
Section: Infectious Diseases Modelsmentioning
confidence: 99%
“…Li et al (2012) found that tree shrews are susceptible to Staphylococcus aureus and Pseudomonas aeruginosa . Zhan et al (2014) infected Chinese tree shrews with Mycobacterium tuberculosis and found that infected animals developed serious symptoms similar to the clinical signs of active tuberculosis observed in humans.…”
Section: Infectious Diseases Modelsmentioning
confidence: 99%
“…Moreover, the tree shrews has been increasingly used as a viable model animal, and are proposed to be an alternative experimental animal to rodents and primates in biomedical research, as they have several characteristics including low cost of maintenance, small adult body size, high brain-to-body mass ratio, a short reproductive cycle, and can be more easily obtained than monkeys (Cao et al, 2003; Fuchs and Corbach-Söhle, 2010; Fan et al, 2013, 2014; Xu et al, 2013). In addition to Alzheimer’s disease (Yamashita et al, 2010; Lin et al, 2016), the tree shrew has also been successfully used as an animal model of liver disease (Zhao et al, 2002), depression (Wang et al, 2011), myopia (Norton et al, 2006), bacterial infection (Li et al, 2012) and learning behaviors (Bartolomucci et al, 2002). Hence, the tree shrew has the potential to serve as a viable model for cell transplantation in translational studies examining SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Various significant findings have been obtained in Chinese tree shrew models of reproductive, immunologic and social‐psychological diseases (Yu et al ., ; Keuker et al ., ; Wang et al ., ). This animal is also used for research on diseases caused by viruses, such as hepatitis A/B/C/D (Guitart et al ., ; Zhao et al ., ; Amako et al ., ), HIV and influenza (Zi‐Feng Yang et al ., ), as well as diseases caused by bacteria, such as Staphylococcus aureus and Pseudomonas aeruginosa (Li et al ., ). However, it is unknown whether Mycobacterium tuberculosis (MTB) could infect Chinese tree shrews and cause disease.…”
Section: Introductionmentioning
confidence: 97%